(untitled) (Research, Society and Development, 2021)
The organizational values ​​serve as parameters for the assessment of behavior, conduct and professional motivation. They are essential elements for the perception and understanding of the organizational culture, especially in companies with a family management structure. Based on the Organizational Values ​​Scale - EVO model, this article aimed to verify the adequacy of the model to professionals working in companies with a family management structure. For this, this Scale was applied to a sample composed of 360 professionals working in family businesses, medium and large, in the state of Rio de Janeiro, in the segments of commerce, industry and services. The evaluation was conducted by means of factor analysis techniques, necessary to validate and test the structural model. Statistical procedures were used to describe the sample regarding the similarity properties between its variables. The results obtained identified sets of variables that configure a model adapted from the structure of organizational values ​​in family businesses, in addition to scales of adjustments necessary to confirm adherence of the model adapted to the original EVO model of the delimited sample. With that, it was possible to answer the central questioning of this research, indicating that the original model, characterized by 38 variables distributed in 5 factors, resulted in an adapted model, characterized by statistical significance (p < 0.05), consistency and quality of the indices (X2/gl = 2,146, GFI = 0,942, AGFI = 0,909, CFI = 0,948, RMSEA (90%IC) = 0,056) obtained by the adjustments, configuring a new structure with 16 variables, distributed in the 5 factors of the original EVO model.